(3GdegeGJ GdeajOI aj TQM GdaQjOIs - (3CHhYHO Gddg eMeO Hf YHO GdQMef Hf RcQj GdaGSjs; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s
(3ChdgG (B:s
(3hHYO, agPG JbjjO fGaY bUOJ Hg Md CdaGX CdajI GdSjhWj s
(3BNQgG (B:s
(3GdNfGS(B: (3GdTjWGf, hGdNJQ(B: (3GdZOQ gPG BNQ eG JjSQ JbjjOg ef gPG GdTQM s
(3GdfSNI LRAGfs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
Keywords: (3GdfMhs